Study on Thermal Stress of Water/Steam Solar Absorber Tubes Under Unilateral Non-uniform Heat Flux Boundary Conditions - Canghong ZHANG; Nan TU; Jiabin FANG (发电技术)
The absorber tubes are subjected to highly non-uniform solar irradiation inside a water/steam solar cavity receiver. This causes the uneven wall temperature and large gradients applied to the absorber tubes, producing thermal deformation and stress, even the damage and failure of the receiver. The typical boiling tube and superheated tube were selected as the research objects. The thermal-structural coupling numerical simulation was carried out by using ANSYS finite element analysis method. The results show that these two types of tubes have significant differences in terms of heat transfer. The radial temperature gradient of the boiling tube leads to the bi-axial thermal stress appearing on the inner and outer walls of its irradiated front side. The circumferential temperature gradient of the superheated tube results in the serious bending deformation and the high axial stress, which also induces the circumferential distribution of equivalent stress. When the concealed back side of the absorber tubes is constrained by supports, the tube bending is significantly improved, and the thermal stress of the superheated tube is no longer circumferential. Furthermore, the axial normal stress component increases greatly and the equivalent stress on the absorber tubes increases by 1.3-6.9 times.